Past shadows and gender roles: Human-elephant relations and conservation in Southern India - Narayan Sharma; Rashmi Singh; Rishi Kumar Sharma; Rohit Negi (Journal of Political Ecology)
Some conceptual thinking about human-wildlife relations has lacked translations into empirical studies with an in-depth enquiry into social, cultural, economic and ecological aspects. This study explores human-elephant relations in a cohabited landscape in the Western Ghats of India, with a focus on 'more than conflict' relations. The Valparai plateau, in the Indian Western Ghats, is a landscape dominated by tea estates and remnants of rainforest fragments where human communities cohabit and closely interact with wildlife. We offer an empirical contribution on the variegated and paradoxical relation between care and fear, between empathy and hate and between the residents and elephants of Valparai. Where conflicts occur between elephants and humans, they have multiple meanings. Gender and unpleasant memories serve as drivers of negative attitudes towards wildlife. A conservation intervention based on engagement and collaboration with local people was perceived as highly effective. Preventive and mitigative, rather than reactive conflict mitigation strategies may have a significant role to play in maintaining the social carrying capacity of local communities towards elephants. We explore the many facets of human-elephant relations, and the numerous entanglements between them, thereby adding multiple layers to the extant knowledge of human-animal relations in the Western Ghats.